Effective Communication and Knowledge Distribution in Healthcare Interaction with Migrants. Issue 9 (29th July 2021) - Baraldi, Claudio; Gavioli, Laura
ABSTRACT: Modern patient-centered approaches increasingly recognize the contribution of patients' knowledge in interactions with health-care personnel. Effective involvement is exceptionally difficult when patients are migrants with limited command of specialized language. Interactional practices that promote effective distribution of knowledge and access to it are needed: by doctors interacting directly with patients in a shared language and by mediators providing interpreting services across different languages. In this paper, we look at two types of sequence which seem to be effective in involving (migrant) patients. The first concerns clinicians' reactions to spontaneous patients' initiatives, like claims to knowledge or personal narratives. The second concerns interpreters' explanations when they render the clinicians' instructions to the patients. While both sequences are clearly designed to promote patients' participation, they need particular communicative competence on the part of staff, clinicians, and interpreters.